Anti-proliferative constituents from Selaginella pulvinata. (March 2016) - Wang, Yan-Dong; Zhang, Jin-Zhi; Wang, Yan-Hua; Yang, Jing; Li, Hai-Yan; Cai, Li-Min
Graphical abstract: Highlights: Two new compounds were isolated from Selaginella pulvinata . Structures were elucidated on the basis of spectroscopic data. Compound1, a new indole derivative, exhibited potent anti-proliferative activity. Abstract: Two new compounds, ( S )-(−)- N -[2-(3-Hydroxy-2-oxo-2, 3-dihydro-1 H -indol-3-yl)-ethyl]-acetamide (1 ) and 6-formyl-5-isopropyl-3-hydroxymethyl-7-methyl-1 H -indene (2), were isolated from the leaves of Selaginella pulvinata . Their structures were determined by spectroscopic methods. Additionally, compound1 could inhibit the growth of SK-mel-110 cells and induce cell apoptosis in vitro through up-regulating the expression of inhibitor of growth family member 4.